Landslide Zone Investigation by Determining Cracks and Cracks Compressive Strength Test in Waru District, Pamekasan Regency - sandy vikki ariyanto; Idon Joni (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
Landslide zone investigation has been conducted using geoelectricity to determine the number of cracks and using a compressive strength test to determine compressive strength cracks. The result of this research is that the rock layers of Waru District consist of soil layers resulting from the weathering of quartz rock into quartz sandstone. This quartz sandstone lies on top of a more solid rock layer. The type of landslide that is formed in the Waru sub-district is translational. This type of landslide is caused by water entering the lower layer, causing landslides and the number of cracks that trigger landslides. The results of the low compressive strength test resulted in landslides. This result was due to a decrease in the number of pores filled with water and an increase in the pores that were not filled with water. This occurs due to the presence of water in the cracks, the number of cracks cavities, and the density of the cracks which results in reduced adhesion between the cracks holding layers.